Tratamento de água residuária da atividade automotiva por ozonização convencional e catalítica - Paula, Luciene Oliveira de (2014)
The car wash is an activity that uses large volumes of water and generates effluents which have turbidity, chemical oxygen demand (COD), color and the presence of surfactants and oils and greases high, giving it high potential as a pollutant. In this context, the potential of the process of conventional and catalytic ozonation for residual water treatment of vehicle washing was evaluated taking into account mainly the increase of the biodegradability of organic compounds. For this purpose, we assessed conventional ozonation effects on the following parameters: true color, turbidity, alkalinity and COD, for different values of pH. Catalytic ozonation was also evaluated in respect to the addition of activated carbon in reaction medium. In order to evaluate the actual oxidation of organic matter that occurred during the process of ozonation, studies of stripping of volatile gases through the bubbling compressed air and pure oxygen were performed using minimum stripping. Conventional ozonation was effective especially on effluent discoloration, however, when only ozone was applied into the process it did not reach a high effluent mineralization degree, which was evidenced by low reduction of COD parameter. Activated carbon addition increased the removals efficiencies for all parameters analyzed. This fact allows us to conclude that activated carbon was able to catalyze the decomposition of molecular ozone in highly reactive species in the aqueous phase, as the hydroxyl radical, as well as acting as adsorbent in the process.